Entrainment and impingement of juvenile silver perch, Bidyanus bidyanus, and golden perch, Macquaria ambigua, at a fish screen: effect of velocity and light. (18th February 2013) - Boys, C. A.; Baumgartner, L. J.; Lowry, M.
Abstract: Entrainment and impingement of two non‐salmonid species susceptible to entrainment at irrigation diversions, silver perch, Bidyanus bidyanus (Mitchell), and golden perch, Macquaria ambigua (Richardson), were examined at an experimental intake screen in a laboratory flume under a range of velocities and light levels. The presence of an intake screen significantly reduced entrainment, in some cases reducing mortality from over 90% (unscreened) to less than 2% (when screened). Although some differences in behaviour existed between species, approach velocities (measured 8 cm in front of the screen) up to 0.4 m s −1 effectively reduced entrainment, with very little injury or mortality resulting from incidental screen contacts or impingement. Both species used visual cues to negotiate the screen face, thereby increasing their ability to avoid contact at higher velocities. In the absence of these visual cues, positive rheotactic behaviour was enhanced and fish mostly avoided approaching the screen. These results demonstrate that fish screens operated at approach velocities of up to 0.4 m s −1 have great potential for the protection of silver perch and golden perch juveniles at irrigation intakes.